Dewatering of POME digestate using lignosulfonate driven forward osmosis - Nidal Hilal (Separation and purification technology, 2020)
High demand for palm oil results in the production of huge quantities of palm oil mill effluent (POME) wastewater containing a high amount of organics. Currently, this is often processed by anaerobic fermentation, but the waste water still requires further processing. Dewatering of POME digestate could simultaneously recover nutrients for use as organic fertiliser and treat water sufficiently to allow other uses. This work investigates the feasibility of using a forward osmosis (FO) process driven by lignosulfonate draw solutions. It was found that water fluxes for pure water and simulated POME digestate feeds were lower for lignosulfonates than NaCl as draw solutes, but had much lower reverse solute fluxes. Reverse solute flux is of great importance for dewatering of POME digestate, as concentration of salts in the dewatered feed will preclude their use as organic fertilisers. Na lignosulfonate showed both higher water fluxes and lower reverse solute flux than the Ca lignosulfonate. Water fluxes when using the simulated POME digestate were lower than predicted from the directly measured osmotic pressures of the solutions, suggesting increased membrane resistance due to fouling or concentration polarisation effects. In addition, osmotic pressures of organic solutions were measured directly from dead-end filtration measurements. This showed that the relationship between osmolality measured from freezing point depression measurements and osmotic pressure of solutions varies for different solutes, suggesting that osmolality measurements do not give a reliable measure of osmotic pressure when comparing different organic solutions.